Toxicity effect of Centella asiatica Linn. extract on mice (Mus musculus) organ and tissue - ., Praptiwi; Wulansari, Dewi; ., Chairul (Indonesian Journal of Pharmacy, 2010)
Toxicity test ofCentella asiaticaLinn. water extract had been carried out. Extract  were  administered  via  oral,  single  and  daily  doses  in  mice  (Mus musculus).  The  effect  of  extract  on  organs  and  tissue  were  evaluated  by observing  the  pathology  anatomy  of  heart,  liver  and  kidney  and  alsoLD50 value. The influences of acute and sub-chronic toxicity on morpho-anatomy organs and histo-pathology tissue were in accordance with LD50experiment. The results of morpho-anatomy showed that all organs were still in normal condition at  low  dose  treatment,  but stain  and  white  spots  appeared  on  liver, black  spot on  heart  and  white  spots  on  kidney  at  higher  dose.  Histo-pathology  indicated that low dose administration of extract resulted that, all of tissue observed were in  good  and  normal  condition,  but  at  higher  dose  resulted  injure  of   muscle fibres  and  also  injure  of  nucleus  cells  of  heart  tissue  also  the  colour  of  liver tissue  was  brick  red  and  white  stain  manifestation  (because  the  damaged  of cells  and  accumulation  of  leucocytes).  Degeneration  and  congestive  sinus occurred  in  liver  tissue,  while  necrosis  and  protein  degeneration  formed  in kidney  because  of  glomerulus  membrane  damaged.  LD50 of Centella extract was  13.6  g/kg.  This  dose  indicated   that  Centella  extract   is   slightly   toxic (5 - 15 g/kg), so that it is suggested that if it was used in phyto-therapy had to be under supervision of an expert or specialist and administered in low dose and short period.Keywords : Centella  asiatica Linn;  extract;  acute  and  subchronic  toxicity;  anatomy pathology